LAYANAN BIMBINGAN KLASIKAL UNTUK SISWA KELAS X YANG MEMILIKI KEPERCAYAAN DIRI RENDAH SMA ASSHIDDIQIYAH GARUT - Dina Siti Rohmah; Wikanengsih Wikanengsih; Muhamad Rezza Septian (IKIP Siliwangi, 2021)
The purpose of this study was to determine the classical guidance service for class X students who have low self-confidence in SMA Asshidiqiyah Garut. The method used is descriptive qualitative research type case study research. The subjects in this study were 4 students who experienced low self-confidence. Techniques in data collection are interviews, observation, and documentation. The results of research on classical guidance services for class X students who have low self-confidence in SMA Asshiddiqiyah Garut. Helping students in their development process. Provide support and positive influence for students to appear more confident. The response of students is able to bring positive things related to the self-confidence giving process by the guidance and counseling teacher. Barriers related to the implementation of classical guidance services for students who have low self-confidence in SMA Asshiddiqiyah are lack of understanding of the material that the guidance and counseling teachers convey to students, so that students are hampered in the process of receiving classical guidance services for low self-confidence.Keywords: : classical guidance,confidence